2009
DOI: 10.1016/j.biomaterials.2008.12.053
|View full text |Cite
|
Sign up to set email alerts
|

The effect of collagen I mimetic peptides on mesenchymal stem cell adhesion and differentiation, and on bone formation at hydroxyapatite surfaces

Abstract: Integrin-binding peptides increase cell adhesion to naive hydroxyapatite (HA), however, in the body, HA becomes rapidly modified by protein adsorption. Previously we reported that, when combined with an adsorbed protein layer, RGD peptides interfered with cell adhesion to HA. In the current study we evaluated mesenchymal stem cell (MSC) interactions with HA disks coated with the collagen-mimetic peptides, DGEA, P15 and GFOGER. MSCs adhered equally well to disks coated with DGEA, P15, or collagen I, and all thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
159
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(173 citation statements)
references
References 60 publications
6
159
0
Order By: Relevance
“…Fellah et al (2007; recently reported that the inflammatory cytokines, e.g., IL-6 and TNF-α, released by macrophages stimulated by BCP microparticles, may have both positive and negative effects on new bone formation. However, the very little related research that labelled the marker molecules expressed by the osteocytes or osteoblasts has been performed and was most likely due to the limitation of animal models to some extent (Hennessy et al, 2009). In this study, we observed bone formation in the mice model and our results may contribute to further mechanism studies based on the modern biotechnologies developed in the mice model.…”
Section: Discussionsupporting
confidence: 56%
“…Fellah et al (2007; recently reported that the inflammatory cytokines, e.g., IL-6 and TNF-α, released by macrophages stimulated by BCP microparticles, may have both positive and negative effects on new bone formation. However, the very little related research that labelled the marker molecules expressed by the osteocytes or osteoblasts has been performed and was most likely due to the limitation of animal models to some extent (Hennessy et al, 2009). In this study, we observed bone formation in the mice model and our results may contribute to further mechanism studies based on the modern biotechnologies developed in the mice model.…”
Section: Discussionsupporting
confidence: 56%
“…Many researchers have shown that protein adsorption is an important determinant of cell adhesion in early phases. Also, initial cell adhesion is critical for the functional improvement of anchorage-dependent cells because it mediates subsequent cellular responses, including proliferation and differentiation [3,[44][45][46][47] . In this study, our main objective was to evaluate the influence of nHA on osteogenic induction in USSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Mimetic peptides, such as those containing the GlyPhe-hydroxyproline-Gly-Glu-Arg (GFOGER) and Asp-GlyGlu-Ala (DGEA) motifs of collagen, mediate the functions of integrin subtypes in the non-RGD pathway. 42 Although polypeptides and mimetic peptides both reasonably promote the adhesion of cells onto material surfaces, they have limited function in the chondrogenic differentiation of seed cells. In this study, we used a heterologous chimeric fusion protein (rFN/Cad-11) that was designed to cover FNIII7-10 and the FIG.…”
Section: Discussionmentioning
confidence: 99%